PENGARUH MATERIAL BILAH DAN KECEPATAN ANGIN TERHADAP PERFORMANSI TURBIN ANGIN HORISONTAL SKALA MIKRO - Mahfudz Fahrudin; Husin Bugis; Herman Saputro (Nozel : Jurnal Pendididikan Teknik Mesin, 2020)
The availability of fossil fuels in Indonesia has recently been running low due to exaggerated use of the fuel. To fulfill the electrical energy needs of the community which more environmentally friendly used, wind turbines can be used. In this study, researchers use a micro-scale horizontal axis wind turbine from wood and composite materials on the blades, where it try to determine the effect of each performance. This study uses an experimental method which is carried out at the Wind Tunnel Laboratory of the Mechanical Engineering Education, Sebelas Maret University. The variables are blades with a variety of composite and wood material. Performance of electrical power is investigated in this research. Data shows that the wind speed 5m/s - 6m/s composite without load produces the highest rotate, which is 544.64 rpm. While, wood material take lower at 494.2 rpm. The wind turbine is driven at 5 m/s – 6 m/s by using 12V of load. It produces 367.68 rpm and 6.771 watts for composites, and 303.6 rpm and 5.047 watts for wood. So it can be concluded blade materials could effect to the turbine performance.